8. usun nawiasy i zredukuj wyrazy podobne
a)5x+(2x-7)-9x-(-3x+8)+20-8x
b)-5x+(-2y+4x)-(7x-8y)-x+(2-6y)
c)-9z-(4-3z)-8y-(-7z+8y)+(-2y-7)

10.
a)-y+8x-z-2x dla x=-2,y=6,z=-3
b)-8y-4z+x-y-2z+1 dla x=-,05,y=-1,z-2
c) 9y-(7y+x)+(6x-7y) dla x=-2,y=3
d)(6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2,b=0,1


DAM NAJ!

3

Odpowiedzi

2010-02-17T18:36:01+01:00
8
a) =5x+2x-7-9x+3x-8+20-8x= -7x+5
b) =-5x-2y+4x-7x+8y-x+2-6y=-9x+2
c) =-9z-4+3z-8y+7z-8y-2y-7= z-18y-11

2 4 2
Najlepsza Odpowiedź!
2010-02-17T18:47:08+01:00
8.
a)5x+2x-7-9x+3x-8+20-8x=-7x+5
b)-5x-2y+4x-7x+8y-x+2-6y=-9x+2
c)-9z-4+3z-8y+7z-8y-2y-7=z-18y-11
10.
a)-6-16+3+4=-15
b)8+8-0,5+1+4+1=21,5
c)9y-7y-x+6x-7y=-5y+5x=15-10=5
d)6a-8b-0,7-6,9-a+5b+1,8=5a-3b-5,8=1-0,3-5,8=-5,1
  • Użytkownik Zadane
2010-02-17T19:00:03+01:00
8
a) 5x + (2x-7) -9x - (-3x+8) + 20 - 8x = 5x + 2x - 7 - 9x + 3x - 8 + 20 - 8x = -7x + 5

b) -5x + (-2y+4x) - (7x-8y) - x + (2-6y) = -5x - 2y + 4x - 7x + 8y - x + 2 - 6y= -9x + 2

c) -9z - (4-3z) - 8y - (-7z+8y) + (-2y-7) = -9z - 4 + 3z - 8y + 7z - 8y - 2y - 7= z - 18y -11



10.
a) -y + 8x - z - 2x dla x= -2, y= 6, z= -3

- 6 - 8 * (-2) - (-3) - 2 * (-2) = -6 -16 + 3 + 4 = - 15

b)-8y - 4z + x - y - 2z + 1 dla x= -0,5, y=- 1, z= -2

-8 * (-1) - 4 * 9-2) + (-0,5) - (-1) - 2 * (-2) + 1 = 8 + 8 - 0,5 + 1 + 4 + 1 = 21,5

c) 9y-(7y+x)+(6x-7y) dla x=-2,y=3

9*(-2) - ( 7*3 + (-2) )+ ( 6*(-2) - 7*3 ) = -18 - (21 - 2) + ( -12 - 21 ) = -18 - 21 + 2 - 12 - 21 = -70


d)(6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2,b=0,1

(6*0,2 - 8*0,1 - 0,7) - (6.9 + 0,2 - 5 * 0,1) + 1 = 1,2 - 0,8 - 0,7 - 6,9 + 0,2 - 0,5 + 1 = -6,5